Intensity-modulated magnetic field sensor based on magnetic fluid and optical fiber gratings - Zheng, Jie (2014)
An intensity-modulated magnetic field sensor based on magnetic fluid and optical fiber gratings is proposed and experimentally demonstrated. The sensor is formed by a tilted-fiber Bragg grating (TFBG) coated by magnetic fluid (MF) and cascaded by a chirped-fiber Bragg grating (CFBG). Transmission of the TFBG is modulated by refractive index of the MF, which is sensitive to external magnetic field. The CFBG is well designed to reflect a broadband of light spectrally located at the cladding mode resonances region of the TFBG. Therefore, reflected optical power is modulated twice by the magnetic field and measurement is realized in reflection manner.